2023 GENERAL ELECTIONS, POLITICAL VIOLENCE AND NATIONAL INTEGRATION IN NIGERIA: A STUDY OF LAGOS STATE EXPERIENCE - AHMED OLAWALE MOLIKI; PETER ADENIYI Oluwatobi (International Studies Journal)
This paper investigated nexus between the 2023 general elections, political violence and national integration in Nigeria, focusing on Lagos State’s experience. The study specifically examined the factors that promoted political violence during the 2023 general elections and its implication on national integration in Lagos State Nigeria. The descriptive survey research design was adopted while self-structured questionnaire was utilised to elicit data from 215 respondents. The data were analysed with mean and standard deviation. The study discovered that several composite factors such as politics of sentiment and entitlement (Emilokan - it is my turn - mantra), excessive monetised politics, religiosity, ethnicised politics and power shift syndrome, among others, promoted the political violence witnessed during the general elections in Lagos State. Equally, the study revealed that political violence witnessed in Lagos State during the 2023 general elections further wrecked havoc on the already cracked and disunity relationship among the ethnic groupings residing in Lagos State as the elections breed sentiment, disunity, distrust and threatens friendliness, tolerance, economic activities and democracy in the state. The study concluded that political violence witnessed during the 2023 general elections distorts peaceful co-existence of the major ethnic constituents in Lagos State and further widen gap of promoting national integration in the State and Nigeria at large. It was recommended among others, that the stakes of the elections should be made less attractive so as to give room for patriotic citizens to participate in the political process and curb do-or-die elections.